Common Mental Disorders in Public Transportation Drivers in Lima, Peru - Ruiz-Grosso, Paulo (Public Library of Science, 2014)
BACKGROUND: Traffic related injuries are leading contributors to burden of disease worldwide. In developing countries a high proportion of them can be attributed to public transportation vehicles. Several mental disorders including alcohol and drug abuse, psychotic disorders, mental stress, productivity pressure, and low monetary income were found predictors of high rates of traffic related injuries in public transportation drivers. The goal of this study was to estimate the prevalence of common mental disorders in the population of public transportation drivers of buses and rickshaws in Lima, Peru. METHODOLOGY/PRINCIPAL FINDINGS: Cross sectional study. A sample of bus and rickshaw drivers was systematically selected from formal public transportation companies using a snowball approach. Participants completed self-administered questionnaires for assessing major depressive episode, anxiety symptoms, alcohol abuse, and burnout syndrome. Socio demographic information was also collected. The analyses consisted of descriptive measurement of outcomes taking into account both between and within cluster standard deviation (BCSD and WCSD). A total of 278 bus and 227 rickshaw drivers out of 25 companies agreed to participate in the study. BCSD for major depressive episode, anxiety symptoms and burnout syndrome was not found significant (p>0.05). The estimated prevalence of each variable was 13.7% (IC95%: 10.7–16.6%), 24.1% (IC95%: 19.4–28.8%) and 14.1% (IC95%: 10.8–17.4%) respectively. The estimated prevalence of alcohol abuse was 75.4% (IC95%: 69–81.7%, BCSD = 12.2%, WCSD = 41.9%, intra class correlation (ICC): 7.8%). CONCLUSION: Common mental disorders such as alcohol abuse, major depressive episode, anxiety symptoms and burnout syndrome presented higher rates in public transportation drivers than general population.